Análisis de la evolución de la asequibilidad del cigarrillo en Suramérica 2000-2009 (2010)
Price policies are recognized as the single most effective measure for tobacco control. This study provides updated information for Colombia and a group of Latin American countries that were selected either because they are important references from the point of view of illegal trade flows or beacuse they reflect the spectrum of tabaco tax policies in the region. The indicator of interest is the affordability of cigarettes, measured on an annual basis for the period 2000-2009 using two of the most common methodological approaches in previous studies: the equivalent in labour minutes and the percentage of GDP that represents the value of 100 packs (Relative Income Price). The results show that Colombia has the lowest price level of the sample and that cigarettes have become cheaper over the analysis period. This suggests that there is space to raise taxes much higher than currently recognized by the Government, as revealed by the political debate of recent tobacco products tax reform.